Tactical marketing decisions of managers in times of crisis Qatar Airways Company, Grounded Theory - Omarli Sevinj (Proceedings of the Central European PhD Workshop on Technological Change and Development, 2020)
This research study is conducted with the primary aim of exploring tactical marketing decisions of managers in times of crisis; using Qatar Airways Company as a sample. The main purpose of the study is to determine which factors impact on the tactical marketing decisions of managers and what marketing activities are applied in times of crisis. The interviews with marketing information executives were analyzed using grounded theory methodology. Data analysis in the study followed Strauss and Corbin (1990) coding processes. 4500 coding materials were analyzed in two interviews. Results indicated that four major components marketing strategy of a company, marketing informational system (MIS), environmental factors, and internal restrictions and limitations of the company - play important roles in the decision-making process of managers in the crisis period. It was determined that if a company makes tactical promotional decisions such as proposing new campaigns, placing advertisements at local websites and tourism agencies, allocating budget for promoting the website as a sales channel, they will get positive outcomes during crisis periods.